Expansion of Dolomitic Rocks in TMAH and NaOH Solutions and Its Root Causes - Yuan, Huan (Materials (Basel), 2020)
In this paper, a tetramethylammonium hydroxide (TMAH) solution and homemade cement without alkali were used to eliminate the influence of the alkali-silica reaction (ASR) on the expansion of dolomitic rocks, and a NaOH solution was used as a comparison agent. The expansion of concrete microbars and dolomite powder compacts prepared from dolomitic rocks was tested. The expansion cracks and reaction products were investigated by X-ray diffraction, optical microscopy, scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS). The results showed that TMAH reacts with dolomite crystals in dolomitic rocks to form brucite and calcite. Through X-ray diffraction and SEM-EDS analysis, it can be determined that the chemical reaction between TMAH and dolomite crystal was dedolomitization. The expansion stress test and concrete microbar expansion test suggest that the alkali carbonate reaction (ACR) can produce expansion. Although both the ASR and the ACR were observed in the NaOH reaction system, but ASRgel was not found in the cracks, indicating that the ASR may be involved in the expansion process of concrete microbars and that the ACR is the root cause of the expansion. However, under the curing conditions of the TMAH solution, many ACR products were found around the crack, indicating that the expansion of the concrete in this system was caused entirely by the ACR.